Sensate hypothenar perforator free flap for resurfacing large volar surface defect of the digit. Issue 4 (4th September 2016) - Seo, Bommie Florence; Kwon, Byung Yeun; Han, Hyun Ho
Abstract: In this report we present a case of large sized volar surface defect of a digit reconstructed by hypothenar perforator free flap coverage. A 57‐year‐old male patient presented with a 5 × 2 cm sized avulsive injury on his left little finger involving near total loss of the volar surface. The perforator arteries of the hypothenar area were identified around 5–15% on the x ‐axis and 25–50% on the y ‐axis ( y ‐axis: a line from the pisiform base to the metacarpophalangeal joint, x ‐axis: a line perpendicular to the y ‐axis.) The hypothenar free flap was designed centered on the anticipated location of the perforator artery. Upon dissection, the perforator artery was found as predicted and a superficial palmar vein was saved for venous drainage. In addition, a neighboring cutaneous branch of the ulnar nerve was also saved. The flap survived with satisfactory flap contour, durability, skin color and texture. Five months of follow‐up showed acceptable range of motion for joints of the affected digit and nearly full range of motion for the hand. The sensate hypothenar perforator free flap could be considered as a useful surgical option for large sized volar side defects of finger.